2010
DOI: 10.4314/njps.v22i1-2.54863
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cigarette smoking on intraocular pressure and arterial blood pressure of normotensive young Nigerian male adults

Abstract: Summary:This study was designed to determine the effects of cigarette Smoking on intra ocular pressure and arterial blood pressure of normotensive young male adults. Fifty male students (who met the screening conditions and devoid of obvious ocular pathology and systemic diseases and nonsmokers) had their intra ocular pressure (IOP) measured with a schiotz tonometer and blood pressure(BP) measured with standard syphgmomanometer respectively prior to smoking of two sticks of cigarette each day for one month and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…It has been shown that smoking is linked to an increased risk of developing cataracts, age-related macular degeneration [21], glaucoma [22] and among others. The Beaver Dam study related active smoking (or smoking history) with a higher prevalence of dry eye [23].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that smoking is linked to an increased risk of developing cataracts, age-related macular degeneration [21], glaucoma [22] and among others. The Beaver Dam study related active smoking (or smoking history) with a higher prevalence of dry eye [23].…”
Section: Discussionmentioning
confidence: 99%
“…Also, cigarette smoking is associated with malignant, respiratory, and cardiovascular life threatening diseases [16]. Moreover, smoking reduces the blood flow which aids blood clots formation within the ocular blood capillaries [17]. Such clots prevent the flow of essential nutrients needed to keep the eye healthy [17].…”
Section: Introductionmentioning
confidence: 99%
“…3 People who smoke cigarettes are at an increased risk of developing cataracts, age-related macular degeneration, diabetic retinopathy, glaucoma, Grave's ophthalmopathy, and optic neuritis. 4 Different epidemiological studies conducted shows that there is a dose response relation ship between smoking and development of nuclear cataract. 15 Studies have shown that the cessation of smoking reduces the risk of nuclear opacity, but these findings are not conclusive.…”
mentioning
confidence: 98%
“…2 Smoking also affects the eyes, the toxins associated with smoking decrease blood flow or aid in the formation of clots within ocular capillaries, thus cutting off vital nutrients that are essential for eye health. 3,4 Free radicals that are produced because of smoking impair the normal functionality of the cells and have been reported to cause ocular diseases. 3 People who smoke cigarettes are at an increased risk of developing cataracts, age-related macular degeneration, diabetic retinopathy, glaucoma, Grave's ophthalmopathy, and optic neuritis.…”
mentioning
confidence: 99%